Textile-Based Thermally Driven Actuators for Soft Robotic Mechanotherapy Applications - KOÇAK, EMİNE DİLARA; TUNÇAY ATALAY, ASLI; ÇELEBİ, MEHMET FATİH (My University, 2022)
Rigid-body industrial robotic manipulators and pneumatic compression systems are widely used in mechano-therapeutic applications. However, rigid and bulky components reduce the wearability of the system in mobile environments. The current trend in wearable robotics tends to build such devices using textiles/silicone materials thanks to their lightness, compliancy, and comfort properties. In this study, thermally powered soft fluidic actuators that utilize liquid/gas phase transition property of low boiling point liquids are investigated. Proposed actuators generate desired pressure level and have great potential to free mechano-therapy devices from such bulky components. The developed structure incorporates textile-based heaters, thin film actuator shells, and low boiling point liquids. Here, two low boiling liquids with different boiling temperature are mixed successfully in order to obtain desired boiling point. Results a revealed that actuators constructed with PE/PA membrane did not show any deterioration even after 500 cycle actuation. In order to control the system, instantaneous temperature of the textile-based heater on the actuator device is used as feedback for the on-off controller.
Keywords: Biyomedikal Mühendisliği; Rehabilitasyon; Elektrik-Elektronik Mühendisliği; Elektronik; Devre Kuramı; Elektronik Devreler; Tekstil Mühendisliği ve Teknolojisi; Tekstil Malzemeleri; Tekstil Tasarımı; Mühendislik ve Teknoloji; Biomedical Engineering; Rehabilitation; Electrical and Electronics Engineering; Electronic; Circuit Theory; Electronic Circuits; Textile Engineering and Technology; Textile Materials; Textile Design; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; MÜHENDİSLİK, BİYOMEDİKAL; MALZEME BİLİMİ, TEKSTİL; Engineering, Computing & Technology (ENG); ENGINEERING; MATERIALS SCIENCE; ENGINEERING, ELECTRICAL & ELECTRONIC; ENGINEERING, BIOMEDICAL; MATERIALS SCIENCE, TEXTILES; Sinyal İşleme; Biyomedikal mühendisliği; Elektrik ve Elektronik Mühendisliği; Biyomühendislik; Fizik Bilimleri; Signal Processing; Electrical and Electronic Engineering; Bioengineering; Physical Sciences